The effectiveness of the McCarthy model in developing mental motivation and learning the accuracy of the tennis serve and the center smash (4) volleyball skills for students (Damu Journal of Sport Sciences, 2024)
One of the objectives of the study is to prepare and apply educational units according to the McCarthy model and to identify its effectiveness for developing mental motivation and learning the accuracy of the skills of the tennis serve and the center-reel smash (4). An airplane for students and knowing which is the best model, the McCarthy model or the teacher model, to be followed in the research variables. The two research hypotheses included the existence of differences Statistically significant between the results of the pre- and post-tests for the two research groups on developing mental motivation and learning the accuracy of the tennis serve skills and the smash hit from the 4th center of the volleyball, and there were statistically significant differences between the two groups The results of the post-tests on developing mental motivation and learning the accuracy of the tennis serve and center smash skills (4) First off, an experimental approach was used because it was appropriate to the nature of the research. The sample included fifth-grade biology students in (Aana for Boys) for the academic year (2022-2023). Their number reached (40) students, who were divided into two groups, a control group represented by Division (B) and an experimental group (c Each group consisted of (20) students, who were given pre-tests on the mental motivation scale and the skills of the tennis serve and the center smash (4). The control group implemented the subject teacher’s model and the experimental group implemented the Enmo This is McGarthy model. The educational curriculum was implemented in (10) weeks and as an educational lesson per week and the time of each lesson (40 minutes), The researcher processed the results of his study through the use of statistical methods, and concluded that the McGarthy model and the subject teacher model are two models with positive effectiveness in developing mental motivation and learning the accuracy of the two skills investigated, with varying proportions, and that the McGarthy model is more effective There was no clear development of the variables of the study, and the researcher recommended the need to pay attention to the educational curriculum in accordance with this model and games. Another band.